Me and Sam-Sam handle the apocalypse - Vaught, Susan, 1965- (Simon & Schuster Books for Young Readers, 2020)
Alternates between the detective work of middle-schooler Jesse and her new friend, Springer, after her father is accused of stealing, and post-tornado rescue efforts of Jesse and her Pomeranian, Sam-Sam.